2009
DOI: 10.1016/j.nbd.2008.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Low dose rotenone treatment causes selective transcriptional activation of cell death related pathways in dopaminergic neurons in vivo

Abstract: Mitochondrial complex I inhibition has been implicated in the degeneration of midbrain dopaminergic (DA) neurons in Parkinson’s disease. However, the mechanisms and pathways that determine the cellular fate of DA neurons downstream of the mitochondrial dysfunction have not been fully identified. We conducted cell-type specific gene array experiments with nigral DA neurons from rats treated with the complex I inhibitor, rotenone, at a dose that does not induce cell death. The genome wide screen identified trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 63 publications
2
39
0
Order By: Relevance
“…1c, d) or in other brain regions (not shown). The selective decrease of TH in the substantia nigra and striatum was in line with the known sensitivity of nigro-striatal dopaminergic neurons to rotenone toxicity (Sherer et al 2003b;Meurers et al 2008). To confirm that the observed decrease of TH levels was actually related to degeneration of nigro-striatal dopaminergic neurons and that VPA protected these neurons from rotenone toxicity we sought evidence from different experimental approaches.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…1c, d) or in other brain regions (not shown). The selective decrease of TH in the substantia nigra and striatum was in line with the known sensitivity of nigro-striatal dopaminergic neurons to rotenone toxicity (Sherer et al 2003b;Meurers et al 2008). To confirm that the observed decrease of TH levels was actually related to degeneration of nigro-striatal dopaminergic neurons and that VPA protected these neurons from rotenone toxicity we sought evidence from different experimental approaches.…”
Section: Resultssupporting
confidence: 58%
“…The model and the reasons for the peculiar sensitivity of nigro-striatal dopaminergic neurons to brain concentrations of rotenone that only partially inhibit mitochondrial complex 1 have been discussed elsewhere (Sherer et al 2003b). Furthermore, a recent study has confirmed, at the level of regulation of gene expression, the preferential response of these neurons also to sub-toxic doses of rotenone (Meurers et al 2008). In the present study, by using a standard dosage of rotenone administration (3 mg/Kg/day), continuously delivered through osmotic mini pumps, and by limiting the time of exposure to 7 days, we were able to obtain a sizable decrease of dopaminergic markers in the substantia nigra and striatum of the treated rats and to significantly revert the effect of the neurotoxic insult through chronic dietary administration of VPA that results in blood concentration of the drug close to the human therapeutic window (Hao et al 2004).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Snap frozen brains from the following groups were used for transcriptome analysis (n=5 each): wildtype + control, wildtype + TRO19622, Thy1-aSyn + control, Thy1-asyn + TRO19622; wildtype + control, wildtype + TRO40303, Thy1-aSyn + control, Thy1-asyn + TRO40303. For laser-capture microdissection (LCM) of TH-positive neurons, the substantia nigra was cut in 10 μm serial coronal sections and quickly immunostained for TH as described previously (Meurers et al, 2008; Richter et al, 2009) with adaptation for immunofluorescent staining as follows: following ethanol fixation for 1 minute, sections were incubated with a primary antibody recognizing TH (rabbit anti TH, 1:200, Millipore, Billerica, MA) for 2 minutes followed by incubation for 2 minutes in Cy3 conjugated goat anti-rabbit secondary antibody (1:200, Vector Laboratories, Burlingame, CA) on ice. Sections were rinsed in sterile ice-cold 1x PBS between each incubation step.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial dysfunction is believed to play a prominent role in the etiology of PD, as patients with sporadic PD display systemic mitochondrial complex-1 dysfunction (Mizuno et al, 1989;Nicklas et al, 1985;Parker et al, 1989;Schapira et al, 1989). Furthermore, animal models of PD based exclusively on mitochondrial inhibition have revealed that nigrostriatal dopaminergic neurons are highly susceptible to the effects of mitochondrial dysfunction (Betarbet et al, 2000;German et al, 1992;Liang et al, 1996;Meurers et al, 2009;Sherer et al, 2002Sherer et al, ,2003.…”
Section: The Effect Of Tbi On Nigrostriatal Dopaminergic Neuronsmentioning
confidence: 99%